Impact of Peer Specialist Services on Residential Stability and Behavioral Health Status Among Formerly Homeless Veterans With Cooccurring Mental Health and Substance Use Conditions. Issue 4 (April 2020) - Ellison, Marsha L.; Schutt, Russell K.; Yuan, Lo-Hua; Mitchell-Miland, Chantele; Glickman, Mark E.; McCarthy, Sharon; Smelson, David; Schultz, Mark R.; Chinman, Matthew
Abstract : Objectives: This study tested the impacts of peer specialists on housing stability, substance abuse, and mental health status for previously homeless Veterans with cooccurring mental health issues and substance abuse. Methods: Veterans living in the US Housing and Urban Development—Veterans Administration Supported Housing (HUD-VASH) program were randomized to peer specialist services that worked independently from HUD-VASH case managers (ie, not part of a case manager/peer specialist dyad) and to treatment as usual that included case management services. Peer specialist services were community-based, using a structured curriculum for recovery with up to 40 weekly sessions. Standardized self-report measures were collected at 3 timepoints. The intent-to-treat analysis tested treatment effects using a generalized additive mixed-effects model that allows for different nonlinear relationships between outcomes and time for treatment and control groups. A secondary analysis was conducted for Veterans who received services from peer specialists that were adherent to the intervention protocol. Results: Treated Veterans did not spend more days in housing compared with control Veterans during any part of the study at the 95% level of confidence. Veterans assigned to protocol adherent peer specialists showed greater housing stability between about 400 and 800 days postbaseline. Neither analysis detected significant effects for the behavioral health measures. Conclusions: Some impact of peer specialist services was found for housing stability but not for behavioral health problems. Future studies may need more sensitive measures for early steps in recovery and may need longer time frames to effectively impact this highly challenged population. Abstract : Supplemental Digital Content is available in the text.